Complications of gastric bypass surgery: review - Yuabova, Marina (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2015)
Literature review primarily focuses on the methods associated with reducing post operation complications that can occur as a direct result of gastric bypass surgery. These complications encompass nutritional deficiencies, internal hemorrhaging, hernias, possible bowel obstructions, venous thromboembolism and even infections in some cases. It is due to this that this paper delves into the various methods that can be utilized in order to address these complications in a reasonable fashion.